2006
DOI: 10.1111/j.1460-9568.2006.05001.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of peripheral Na+ channels in triggering the central excitatory effects of intravenous cocaine

Abstract: While alterations in dopamine (DA) uptake appear to be a critical mechanism underlying locomotor and reinforcing effects of cocaine (COC), many centrally mediated physiological and affective effects of this drug are resistant to DA receptor blockade and are expressed more quickly following an intravenous (i.v.) injection than expected based on the dynamics of drug concentration in the brain. Because COC is also a potent local anesthetic, its rapid action on Na+ channels may be responsible for triggering these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
2

Year Published

2007
2007
2012
2012

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 58 publications
2
26
2
Order By: Relevance
“…Although procaine has only onehundredth the affinity that COC has for the DA transporter (Ritz et al 1987), in experienced users its iv administration fully mimics the initial subjective effects of iv COC (Adinoff et al 1998;Fischman and Schuster 1983). In addition to sensory and affective actions, iv procaine also induces an acute, transient hypertensive response (Pitts et al, 1987) associated with peripheral vasoconstriction (Brown and Kiyatkin, 2006), although acting topically it has an opposite, weak vasodilatative action (Lindoft, 1979; Willats and Reynolds, 1985).By affecting various central neurons involved in the processing of somato-sensory information and organization of brain activational processes, this rapid and brief "indirect" action of COC can modulate its slow and prolonged "direct" actions on monoamine uptake. Although in vitro studies suggest that uptake inhibition is the primary action of COC (Heikkela et al 1975), after iv administration COC may affect monoamine release via indirect, sensory mechanisms before it reaches the brain.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although procaine has only onehundredth the affinity that COC has for the DA transporter (Ritz et al 1987), in experienced users its iv administration fully mimics the initial subjective effects of iv COC (Adinoff et al 1998;Fischman and Schuster 1983). In addition to sensory and affective actions, iv procaine also induces an acute, transient hypertensive response (Pitts et al, 1987) associated with peripheral vasoconstriction (Brown and Kiyatkin, 2006), although acting topically it has an opposite, weak vasodilatative action (Lindoft, 1979; Willats and Reynolds, 1985).By affecting various central neurons involved in the processing of somato-sensory information and organization of brain activational processes, this rapid and brief "indirect" action of COC can modulate its slow and prolonged "direct" actions on monoamine uptake. Although in vitro studies suggest that uptake inhibition is the primary action of COC (Heikkela et al 1975), after iv administration COC may affect monoamine release via indirect, sensory mechanisms before it reaches the brain.…”
mentioning
confidence: 99%
“…Like COC, iv procaine induces strong sensory and subjective effects in drug-naive individuals (Servan-Shreiber et al, 1998), sympathoexcitation (Pitts et al, 1987a, rapid EEG desynchronization (Adamec and Stark-Adamec, 1987;Parekh et al, 1995) and brain hyperthermia (Brown and Kiyatkin, 2006). COC-methiodide (COC-M), which cannot cross the blood-brain barrier (Shriver and Long, 1971) also mimics COC in its sympathoexcitatory (Dickerson et al, 1999) and brain hyperthermic effects (Brown and Kiyatkin, 2006), indicating the involvement of peripheral mechanisms.The rapid and transient nature of some subjective and physiological effects of iv COC also point toward possible involvement of peripheral neural elements and rapid neural transmission. Cocaine-induced euphoria (Fischman and Shuster, 1983; Zernig et al, 2002), EEG desynchronization (Lukas et al, 1990Matsuzaki et al, 1978), acute increase in arterial blood pressure (Poon and van den Buuse, 1992) and peripheral vasoconstriction (Kiyatkin and Brown, 2005) all occur within seconds after iv COC injection.…”
mentioning
confidence: 99%
“…Cocaine was injected via catheter and extending tubing, in low volume and at low speed, and special care has been taken to exclude any possible sensory cues associated with drug injection. Although the complexity of VTA cell recording in the awake conditions made it difficult to evaluate the effects of saline on each cellular subgroup, we previously showed that such injections performed at the same conditions did not affect animal behavior, brain, skin, and muscle temperatures (Brown and Kiyatkin, 2006) as well as impulse activity of striatal neurons (Kiyatkin and Brown, 2007). No effects of low-volume saline injections on VTA cell activity have been also documented in our heroin self-administration studies (Kiyatkin and Rebec, 2001).…”
Section: Discussionmentioning
confidence: 62%
“…All these effects, moreover, are generally resistant to DA receptor blockade and in cocaine-experienced subjects they could be mimicked by procaine (Adamec and StartAdamec, 1987;Adinoff et al, 1998;Fischman and Schuster, 1983;Gawin 1986;Sherer et al, 1989), which is not an inhibitor of monoamine uptake, suggesting a leading role of peripheral non-DA neural mechanisms in its mediation. Some of rapid, centrally mediated effects of cocaine, moreover, are mimicked by cocaine methiodide (Dickerson et al, 1999;Brown and Kiyatkin, 2006), which cannot cross the blood-brain barrier.…”
Section: Functional Implications: Sensory Effects Of Cocaine and Theimentioning
confidence: 99%
See 1 more Smart Citation